Social innovation dynamics in the development of public transport apps in South Africa - Muneri, Maanda (My University, 2022)
Innovation within the public transport sector has increasingly been focused on increasing access to excluded groups in an attempt to redress the socio-economic inequalities. However, the modalities of innovation seem to be at odds with this ambitious goal. The study aimed to explore the dynamics of how the targeted end-users of the transport information applications (apps) were engaged during the conceptualisation of the four apps (Khwela, Go-Metro, Gautrain, and Gauteng on the Move), through a qualitative study. Interviews included managers and specialists involved in developing the apps. The primary data was cross-referenced with sentiment analysis of 2,023 user comments. A combination of the social innovation process, Arnstein’s typology of citizen participation, and Amartya Sen’s conceptualisation of development as freedom were used to structure this study. The study found that potential users were barely engaged while developers adopted a corporatist approach to solution development. Furthermore, the sentiment analysis of user comments exhibited growing negative emotions towards the apps. From a perspective of practice, this research suggests new insights into how social innovators might integrate users into the key design steps.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Innovation Studies to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Social innovation; Public transport apps; User feedback; UCTD; SDG-8: Decent work and economic growth